Learning Operating System subject through mobile application for UiTM students / Nor Faranina Aqila Ramlee - Ramlee, Nor Faranina Aqila (2017)
The uses of mobile learning were useful among university students. Mobile learning is said as an educational tool that has the ability to deliver the learning material. Operating System subject is one of the subjects that needs to be presented into interactive multimedia. It is better if the plain text-based learning of courseware can be converted into interactive multimedia elements. The available textbook that does not align with the UiTM syllabus was one of the problems that make students need to search for the other reference books. The time constraints of the operation hour for the library to operate also become one of the difficulties for them to search for the others reference book. Furthermore, the structure of the textbook that contains plain text might not attract students' attention. This Principle of Operating System application is developed to help students to test their understanding in the Operating System subject. This application was develop using ADDIE method where it starts with analysis, design, development, implementation and evaluation. In the evaluations phase, five students are randomly selected to participate as the users to test the mobile application. The students will use the app first and then they will be given questionnaires. The evaluation has been done to test the usability of the application. The feedback from the questionnaires will be used as the scale to improve the Principle of Operating System application. The overall result from the testing shown that most of the participants strongly agree with the usability of the mobile application.